2021
DOI: 10.1108/gm-02-2021-0035
|View full text |Cite
|
Sign up to set email alerts
|

How do personal values help to build generation Y’s entrepreneurial intentions? The role of gender differences

Abstract: Purpose The purpose of this paper is to assess the extent to which personal values affect entrepreneurial intentions and the extent to which this relationship depends on gender among the millennial generation. Design/methodology/approach This relationship was examined using the list of values (LOV). Based on a sample of 600 respondents born between 1977 and 1994, a self-administered online questionnaire was conducted. Findings The partial least squares structural equation modeling (PLS-SEM) approach demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Second, others provide compelling evidence that gender diversity impacts commercial and social EI (Lortie et al, 2017;Molino et al, 2018). Preliminary evidence revealed that women regarded the COVID-19 pandemic as a chance to display greater EI than males (Botezat et al, 2022;Ettis, 2022;Ragazou et al, 2022). However, another researcher supplied compelling evidence demonstrating the display of higher EI by men than women (Birhanu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Second, others provide compelling evidence that gender diversity impacts commercial and social EI (Lortie et al, 2017;Molino et al, 2018). Preliminary evidence revealed that women regarded the COVID-19 pandemic as a chance to display greater EI than males (Botezat et al, 2022;Ettis, 2022;Ragazou et al, 2022). However, another researcher supplied compelling evidence demonstrating the display of higher EI by men than women (Birhanu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…To assess a large research model with several constructs, without enforcing distributional assumptions on the data, several researchers find the PLS-SEM technique to be particularly intriguing. The PLS-SEM was used in several recently published works in a similar context to examine the correlations between native and exogenous variables, such as Nwachukwu et al (2022), Boon et al (2020) and Ettis (2021).…”
Section: Methodsmentioning
confidence: 99%
“…The PLS-SEM was used in several recently published works in a similar context to examine the correlations between native and exogenous variables, such as Nwachukwu et al (2022), Boon et al (2020) and Ettis (2021).…”
Section: Questionnaire Items and Analysis Techniquementioning
confidence: 99%
“…Several previous studies identified that perceived value has significantly influenced customers' behavioral intentions toward restaurants (Hyun et al, 2011;Ryu et al, 2008;Hasan, 2021). However, few studies examined conditional and self-direction value and price fairness as antecedents of intentions (Um and Yoon, 2021;Ettis, 2021;Konuk, 2019). Moreover, no previous study uncovered the impact of perceived value on self-direction value (personal value).…”
Section: Introductionmentioning
confidence: 99%
“…, 2008; Hasan, 2021). However, few studies examined conditional and self-direction value and price fairness as antecedents of intentions (Um and Yoon, 2021; Ettis, 2021; Konuk, 2019). Moreover, no previous study uncovered the impact of perceived value on self-direction value (personal value).…”
Section: Introductionmentioning
confidence: 99%